The Production Model of Tilapia (Oreochromis niloticus) Cultivation with System Dynamics Approach - Ade Kurniawan; Willem Hendry Siegers; Mohammad Aldrin Akbar; Imran Syafei M. Nur (Department of Aquaculture, 2023)
The purpose of this study was to determine the survival rate (SR), the Average Daily Growth (ADG), and the Feed Conversion Ratio (FCR) of Nile tilapia (Oreochromis niloticus) with a dynamic system model. The dynamic system model is used to determine the optimal value of the three variables. The results showed that the survival rate, average daily growth, and feed conversion ratio of tilapia cultivation were 93% (SR), 3.2gr/day (ADG), 0.73 (FCR). In this research, tilapia production were 14,199gr, the amount of feed were 10.344gr and the length of cultivation were 65 days. It was hoped that the dynamic system model design could have tilapia farmers to develop aquaculture businesses that was more environmentally friendly, effective and efficient.